The hotsite usability in the job search process contributes to the positive perception of candidates from the Suzano Mais Emprego Program - Arena, Rafaella Eugenia Mathias (2022)
The current political, economic and social scenario has contributed to the increase in the number of unemployed in recent years and tends to continue growing in the short term. As a result, the number of people seeking reintegration into the labor market increased during the health crisis. Therefore, this paper aims verifying the instruction degree of the professionals who use the Suzano Mais Emprego Program of the Suzano City Hall, and this is a determining factor for the fillment of a web page for visualization and candidacy of the available employment opportunities. Therefore, a social experiment was carried out with the 31 people, followed by an interview based on an application of a questionnaire for data collection. Our results suggest that users with a complete basic education and/or a higher education are able to access and peform the fillment of the web page without many difficulties. Also, it was observed that the knowledge in computing/web browsing is an important feature for the autonomy and usability of the web form for the participants. Hence, we concluded that the creation of a hotsite is viable, provided that some measures are adopted that meet all candidates who use the Suzano Mais Emprego Program services, since the use of digital media in the intermediation of the recruitment and selection process can promote agility in the search for jobs, reduction of waste and exposure to risks of both citizens looking for a job and program employees, and allow the control and statistics report for the Suzano City Hall.